External Debt Statistics : Guide for Compilers and Users. (Manuals and Guides, 2014)
The IMF has released the 2013 External Debt Statistics: Guide for Compilers and Users (2013 EDS Guide), which contains updated global standards for the compilation, reporting, and analytical use of external debt statistics. The 2013 EDS Guide was prepared under the responsibility of the nine organizations in the Inter-Agency Task Force on Finance Statistics (TFFS), in close consultation with national compilers of external debt, balance of payments, and international investment position statistics. [1] The 2013 EDS Guide reflects the significant developments in international finance since the issuance of the 2003 EDS Guide. The 2013 EDS Guide provides guidance on (1) the concepts, definitions, and classifications of external debt data; (2) the sources and techniques for compiling these data; and (3) the analytical uses of these data. The concepts set out in the 2013 EDS Guide are fully harmonized with those of the System of National Accounts 2008 (2008 SNA) and the sixth edition of the IMF's Balance of Payments and International Investment Position Manual (BPM6). [1] The TFFS is chaired by the International Monetary Fund (IMF), and its member agencies are the Bank for International Settlements (BIS), the Commonwealth Secretariat (ComSec), the European Central Bank (ECB), the European Commission (Eurostat), the IMF, the Organization for Economic Co-operation and Development (OECD), the Paris Club Secretariat, the United Nations Conference on Trade and Development (UNCTAD), and the World Bank.